DEVELOPMENT OF A TAZKIYAT AL-NAFS - BASED GUIDANCE AND COUNSELING LABORATORY PROGRAM TO IMPROVE STUDENTS’ COUNSELING PRACTICE SKILLS - Muhammad Putra Dinata Saragi; Rina Suryani; Tengku Atiyah Hanani Binti Tengku Adee Azran; Mutiawati; Atikah Asna (Academic Bright Collaboration, 2026)
This study aims to develop a Tazkiyat al-Nafs-based guidance and counseling laboratory program to enhance counseling practice skills among Islamic Guidance and Counseling students. This study employed a Research and Development approach using the ADDIE model. The program was designed as an eight-session laboratory practicum, with each session lasting approximately 120 minutes. The program integrated counseling skills training, case simulations, role-playing, peer counseling, supervised practice, muhasabah reflection, and competency-based assessment. Thirty-two students were selected through purposive sampling. Data were collected through focus group discussions, interviews, observations, questionnaires, and documentation, and were analyzed to examine validity, practicality, and potential effectiveness. The program was categorized as highly valid, with an average expert validation score of 0.86, and highly practical, with a practicality score of 84.20%. The limited trial showed improvement in students’ counseling practice skills, with the mean score increasing from 68.04 to 84.07, an N-Gain score of 0.52, and a paired-samples t-test result of p < .001. The program may strengthen laboratory-based Islamic counseling training, although the findings are limited by the one-group design, short implementation period, and absence of a control group. This study offers an integrative Islamic counseling laboratory model that operationalizes Tazkiyat al-Nafs through adab, rahmah, muhasabah, supervision, and reflective counseling practice.